A chiral polycyclic aromatic hydrocarbon monkey saddle - Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2020)
A contorted polycyclic aromatic hydrocarbon (PAH) in the shape of a monkey saddle has been synthesized in three steps from a readily available truxene precursor. The monkey saddle PAH is consisting of three five-, seven six-, and three eight-membered rings and has been unambiguously characterized by single-crystal X-ray diffraction. Owing to the three biaryl axes the monkey saddle PAH is inherently chiral. The inversion of the two enantiomeric structures into each other preferably occurs through a twisting of peripheral rings rather than by a fully planar intermediate, as has been calculated by DFT methods. Enantiomers were separated by chiral HPLC and inversion barriers determined by variable temperature circular dichroism spectroscopy, supporting the twisting mechanism.
First published: 15 October 2019
Gesehen am 18.01.2021